PENGEMBANGAN KEPROFESIAN BERKELANJUTAN GURU DALAM MENINGKATKAN MUTU PENDIDIKAN - Mohammad Zainul Arifin Billa (Educational Research Center, 2025)
This study aims to analyze the planning, control, and improvement of the quality of sustainable professional development (PKB) of teachers in improving the quality of education at SMA Plus Miftahul Ulum and SMK Al-Furqon. The quality of educators, as the core of the success of educational institutions, is highly dependent on systematic PKB efforts. With a descriptive qualitative method and a case study approach, data was collected through in-depth observation, structured interviews with key informants, and analysis of literature studies and relevant documents. The results of the study show that PKB planning involves a comprehensive analysis of teacher needs, including performance evaluation and adjustments to the implementation of the Independent Curriculum. Quality control is realized through various PKB programs such as Subject Teacher Meetings (MGMP) and specific training, which is always followed by continuous monitoring and evaluation by school leaders and foundations. PKB quality improvement focuses on identifying post-implementation development needs, utilizing digital technology for distance learning, and career development and professional recognition through certification. The implications of these findings confirm that a planned, controlled, and sustainable PKB is an essential strategy to achieve optimal quality of education, fully supported by the commitment of school and foundation leadership in the context of pesantren-based education.